The Twice Lost - Porter, Sarah, 1969- (Boston, Harcourt Houghton Mifflin Harcourt, 2013)
When humans declare war on mermaids, Luce swims to San Francisco Bay where she finds a group of "twice lost" girls, lost once when trauma turned them into mermaids and again when they defied mermaid law, and unites them into an army under her leadership
Keywords: Mermaids -- California--San Francisco Bay Area -- Paranormal fiction